ACTIVITIES OF FEMALE SCIENTISTS, SCHOLARS IN THE RESEARCH OF TIMUR STUDIES: CHRONOLOGY AND EDUCATION - Yakhshieva Zebo Rashidovna, (KONFERENSIYALAR, 2025)
Abstract.  In this thesis compared the scientific and historical research conducted on the great Uzbek conqueror Sahibkiran Amir Temur. In Particular, Sh. Sh. Alauyeva’s scientific study which is enlightened views of Amir Temur brought to a certain sequence the views advanced in the works  of  other  scholars  and  Orientalists  from  her  target.  We  tried  to  make  new  scientific conclusions  on  the  basis  of  cross-examination  of  scientific  research,  chronological,  typological comparison.